Effects of Thermal Fatigue on Laser Modified H13 Die Steel - Fazliana, Fauzun; S. N., Aqida; Naher, S.; Brabazon, D.; Calosso, Francesco; Rosso, M. (Faculty Mechanical Engineering, UMP, 2014)
In order to improve wear properties of H13 die steel, Thermal fatigue properties of AISI H13 tool steel were investigated at varied number of cycles for enhance surface hardness. A CO2 laser system was used with 0.09 mm focused spot size on the sample surface. The parameter controlled were peak power of 1137 kW and pulse repetition frequency (PRF) of 2300 Hz. Nabertherm model of thermal fatigue machine used consist the cylindrical high temperature furnace with digital control panel, controlled temperature quenching system and pneumatics control sample movement mechanism. The samples were immerge into molten aluminium and quenched in ionized water emulsion at 17oC temperature within specific time per cycle. The quenching system equipped with thermocouple to control the water temperature. The testing was done at 1,750 and 3,500 number of cycles. The treated samples was characterised for metallographic study and hardness. Metallographic study was conducted using optical microscope for laser modified layer thickness and grain size while hardness properties were measured using Vickers indenter. These findings are important to design high wear resistant surface through laser surface modification for semi solid forming dies application.